Epidemiology of Bacterial Keratitis in Lumbini Eye Institute - Gautam, Prachand; Dahal, Polina; Patel, Sushila; Singh, Sweta (Journal of Chitwan Medical College, 2019)
Background: Bacterial keratitis is a common sight threatening condition. Untreated, it often leads to progressive tissue destruction with corneal perforation or extension of infection to adjacent tissue. The aim of the study was to study the epidemiological characteristics of bacterial keratitis seen at Lumbini eye institute in western part of Nepal. Methods: A retrospective study was done from 1st November 2017 to 30th October 2018 in which records of all culture-positive bacterial keratitis over a 1 year period. Data regarding age of patient, occupation, type of injury, coexisting ocular disease was recorded. Clinical evaluation corneal scrapings were collected and subjected to culture and microscopy using standard protocols in all patients. Results: Out of 800 corneal ulcer cases, 305(38.12%) were found to be of bacterial aetiology. A total of 100(32.78%) bacterial pathogens were isolated of which predominant bacterial species Staphylococcus epidermidis 56(56%) followed by Staphylococcus aureus 21(21%), Pseudomonas aeruginosa 12(12%), Streptococcus viridans 5(5%), Nocardia 4(4%) and Streptococcus pneumonia 2(2%) were isolated. Patients with age >45 years were 71(71%) and < 45 years were 29(29%). Among these, (55)55% of patients were non-agricultural workers and (45)45% were farmers; this difference was statistically not significant (p>0.0001). Co-existing ocular diseases predisposing to corneal ulceration were identified only in 19(19%), compared to other predisposing risk factors in 81(81%). Conclusions: The epidemiological characteristic of bacterial keratitis varies geographically. This study describing the features of bacterial keratitis would greatly help the practicing ophthalmologist in the management of their patients.